A poética filosófica e a ciência do sensível: Baumgarten e o nascimento da estética - Silva, Vinícius Vieira (2015)
The presentation of the original sense with which aesthetics was born as a philosophical discipline, in the Alexander Baumgarten’s work, is the central axis of this paper. To this end, we present, firstly, the poetic need for a logic of ingenious thought or for a philosophical poetics, as an alternative to the scientific-mathematical gnosiology of modern racionalist discourse. Thus, this part focuses on presenting and explaining the initial concepts of Baumgarten’s aesthetics referring to the poetic tradition of Aristotle. Forward, we analyse the philosophical-racionalist demand for a theory of sensibility, parallel to the logic of understanding.